برصغیر کا نوآبادیاتی عہد اور تعلیمِ نسواں –ایک جائزہ - Shabana Aman Ullah (Tabeer e Nau, 2025)
During the Mughal era, women’s education was generally limited to the royal and elite classes, with education focused on religious studies, poetry, and basic literacy, while the vast majority of women had no access to formal learning. Women’s education in the pre- and post-colonial subcontinent evolved amidst contrasting societal attitudes, shaped by traditional norms, colonial influence, and reformist movements. In the pre-colonial era, education for women was mostly restricted to elite families and limited to religious instruction, with a few Islamic scholars encouraging female education. The British colonial period introduced Western education, which polarized society–conservative groups opposed it, fearing it would disrupt cultural values, while progressive reformers like Molana Altaf Hussain Hali, Moalana Shebli Noumani, and Deputy Nazir Ahmed supported educating women for societal progress. Christian missionary schools also played a role but had limited influence. As a result, post-colonial saw significant female participation in the Tehreek-e-Pakistan, with leaders like Fatima Jinnah and Begum Ra’ana Liaquat Ali Khan mobilizing women for the cause. This marked a shift towards women’s public involvement, but society remained divided between traditionalists, who resisted women’s education, and more balanced group emerged, promoting women’s education within a framework that respected cultural and religious values, fostering institutions that offered both secular and Islamic education. Women’s contributions helped reshape the role of women and balance between tradition and modernity continues to influence educational policies and women’s empowerment in the region.